An investigation toward purchase intention of halal beef from traditional market: A TPB perspective - Mohammad Khibran (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: The aim of this study was to investigate the consumer behavior toward purchasing intention of halal beef in Yogyakarta traditional Market, by using the Theory of Planned Behavior (TPB) that consisted of attitude behavior, subjective norm and perceived behavioral control, which was moderated by self-identity (religiosity).Methodology: The research used quantitative approach through convenience sampling by using questionnaires, which were distributed to adult Muslim beef consumers from 21-60 years old. In total, there are 110 respondents collected.Findings: The finding of this research showed that the theory of planned behavior (attitude behavior, subjective norm and perceived control behavior) directly influence the purchasing intention toward halal beef in Yogyakarta traditional market, while self-identity (religiosity) moderated the TPB to influence the purchasing intention. Besides, the purchasing intention toward halal beef in Yogyakarta is quite high. It was shown by the high intention to consume halal beef daily.Originality: The lack of published research about the consumption of halal products in Indonesia limits the literature and data for this research. The use of halal logo on beef product sold in traditional market can be applied in this case, both for the butcher and slaughterhouse.